2009
DOI: 10.1139/g09-050
|View full text |Cite
|
Sign up to set email alerts
|

Genetic linkage mapping for molecular dissection of chilling requirement and budbreak in apricot (Prunus armeniacaL.)

Abstract: Commercial production of apricot is severely affected by sensitivity to climatic conditions, an adaptive feature essential for cycling between vegetative or floral growth and dormancy. Yield losses are due to late winter or early spring frosts and inhibited vegetative or floral growth caused by unfulfilled chilling requirement (CR). Two apricot cultivars, Perfection and A.1740, were selected for high and low CR, respectively, to develop a mapping population of F1 individuals using a two-way pseudo-testcross ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
60
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(65 citation statements)
references
References 50 publications
5
60
0
Order By: Relevance
“…Surprisingly, on the BC 2 , these QTLs were not detected in 2001, 2005 and 2006 but were detected with the highest effect in 2007 and 2008 and also with the multi-year analysis, suggesting a higher interaction with climatic conditions for this progeny. In the apricot 'Perfection' , two QTLs controlling chilling requirements and bud break (Olukolu et al, 2009) were also detected on LG6 (Supplementary Figure S1). These results suggest that some of the genes involved in the control of the flowering date may be the same in different species and that chilling requirements and flowering date may be determined by the same or tightly linked genes.…”
Section: Qtl Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…Surprisingly, on the BC 2 , these QTLs were not detected in 2001, 2005 and 2006 but were detected with the highest effect in 2007 and 2008 and also with the multi-year analysis, suggesting a higher interaction with climatic conditions for this progeny. In the apricot 'Perfection' , two QTLs controlling chilling requirements and bud break (Olukolu et al, 2009) were also detected on LG6 (Supplementary Figure S1). These results suggest that some of the genes involved in the control of the flowering date may be the same in different species and that chilling requirements and flowering date may be determined by the same or tightly linked genes.…”
Section: Qtl Analysesmentioning
confidence: 99%
“…These colocalizations suggested that a unique temperature sensor regulates both traits. In apricot, chilling requirements and bud break were analyzed in an F 1 population 'A.1740' Â 'Perfection' and QTLs were detected in all LGs except LG3 and LG4 (Olukolu et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Bud outgrowth did not resume during the period of observation (Oct. to the following Aug.), and most QTL (LOD > 18) in G1 was also detected as a QTL for heat requirement and blooming date, suggesting that there may be one unified temperature sensing system in this region that regulates CR and leads to blooming. In apricot, the use of F 1 pseudo-testcross progenies identified QTLs associated with the CR of vegetative buds, in G1, G2, G3, G5, and G8 (Olukolu et al, 2009). In almond, a major QTL for CR of flower buds was located in G4, and minor QTLs were located in G1, G3, and G7 (Sánchez-Pérez et al, 2012).…”
Section: Seasonal Growth-dormancy Phase Transition Ofmentioning
confidence: 99%
“…In apricot, QTLs analysis of a cross between "Perfection" (high chilling variety) and "A1740" (low chilling variety) showed the most significant QTLs on LG1, LG5 and LG7 (Olukolu et al, 2009);…”
Section: Genetic Studies and Mapping Of Dormancy Associated Locimentioning
confidence: 99%